A transdiagnostic dimensional approach towards a neuropsychological assessment for addiction: an international Delphi consensus study. (5th October 2018) - Yücel, Murat; Oldenhof, Erin; Ahmed, Serge H.; Belin, David; Billieux, Joel; Bowden‐Jones, Henrietta; Carter, Adrian; Chamberlain, Samuel R.; Clark, Luke; Connor, Jason; Daglish, Mark; Dom, Geert; et al.
Abstract: Background: The US National Institutes of Mental Health Research Domain Criteria (RDoC) seek to stimulate research into biologically validated neuropsychological dimensions across mental illness symptoms and diagnoses. The RDoC framework comprises 39 functional constructs designed to be revised and refined, with the overall goal of improving diagnostic validity and treatments. This study aimed to reach a consensus among experts in the addiction field on the 'primary' RDoC constructs most relevant to substance and behavioural addictions. Methods: Forty‐four addiction experts were recruited from Australia, Asia, Europe and the Americas. The Delphi technique was used to determine a consensus as to the degree of importance of each construct in understanding the essential dimensions underpinning addictive behaviours. Expert opinions were canvassed online over three rounds (97% completion rate), with each consecutive round offering feedback for experts to review their opinions. Results: Seven constructs were endorsed by ≥ 80% of experts as 'primary' to the understanding of addictive behaviour: five from the Positive Valence System (reward valuation, expectancy, action selection, reward learning, habit); one from the Cognitive Control System (response selection/inhibition); and one expert‐initiated construct (compulsivity). These constructs were rated to be related differentially to stages of the addiction cycle, with some linked more closely to addiction onset and others more to chronicity. Experts agreed that these neuropsychological dimensions apply across a range of addictions. Conclusions: The study offers a novel and neuropsychologically informed theoretical framework, as well as a cogent step forward to test transdiagnostic concepts in addiction research, with direct implications for assessment, diagnosis, staging of disorder, and treatment.